2020
DOI: 10.1111/sji.12965
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal chemokine CXCL17: What is known and not known

Abstract: CXCL17, the last described chemokine, has recently been found to be abundantly and specifically expressed in mucosal sites, while its receptor is still not well determined. Accumulative studies indicate that CXCL17 could potentially exhibit chemotactic, anti‐inflammatory, antimicrobial activities under multiple biological conditions. However, the mechanism by which it contributes to the physiological and pathological processes within specific mucosal tissues is still far from being fully elucidated. In this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Up to date, 43 chemokines, not counting isoforms, are known in human (2). The latest addition to the chemokine family is mucosal CXC-type chemokine CXCL17 (3). Although the body of literature about CXCL17 is growing and now includes several dozens of published articles focusing on or referring to it, belonging of this protein to the chemokine family remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, 43 chemokines, not counting isoforms, are known in human (2). The latest addition to the chemokine family is mucosal CXC-type chemokine CXCL17 (3). Although the body of literature about CXCL17 is growing and now includes several dozens of published articles focusing on or referring to it, belonging of this protein to the chemokine family remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the recently identified expression of CXCL17 in the kidney 37 , the last identified member of the CXC chemokine family in mammals 38,39 . CXCL17 attracts professional antigen presenting cells 40 , including macrophages, through its receptor (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to the recently identified expression of CXCL17 in the kidney 37 , the last identified member of the CXC chemokine family in mammals 38,39 . CXCL17 attracts professional antigen presenting cells 40 , including macrophages, through its receptor CXCR8. Very little is known about the role of CXCL17 in the kidney but single-cell RNA sequencing analysis revealed that CXCL17 expression is enhanced at an early time point in murine tubulointerstitial fibrosis model 37 . CX3CL1, which binds to CX3CR1, plays a major role in the recruitment of resident macrophage during kidney development 41 and may increase renal macrophage abundance by prolonging their survival 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the expression level of CXCL17 and its receptor CXCR8 in liver carcinoma, breast cancer and colon carcinoma is higher than in adjacent tissues [5][6][7], Saqhir et al found that CXCL17 is one of the upregulated genes in gene expression profile analysis of endometrial cancer patients and healthy people, and its mRNA was detected at a high level in type I endometrial cancer, but no further study was carried out. CXCL17, first discovered in 2006, is a CXC chemokine, that may play a role in the development of endometrial carcinoma, which is named dendritic cell monocyte chemoattractant protein (DMC) or vascular endothelial growth factor-related chemokine-1 (VCC-1) according to its functional characteristics [8]. It has the function of recruiting immune cells, strong anti-inflammatory and antibacterial abilities, chemotaxis, immune dynamic balance regulation and tumor immune response [9].…”
Section: Introductionmentioning
confidence: 99%